Sport and the home front - Taylor, Matthew (Social historian), author.
1 online resource (xiii, 334 pages).
Keywords: "Sport and the Home Front contributes in significant and original ways to our understanding of the social and cultural history of the Second World War. It explores the complex and contested treatment of sport in government policy, media representations and the everyday lives of wartime citizens. Acknowledged as a core component of British culture, sport was also frequently criticised, marginalised and downplayed, existing in a constant state of tension between notions of normality and exceptionality, routine and disruption and the everyday and the extraordinary. The author argues that sport played an important, yet hitherto neglected, role in maintaining the morale of the British people and providing a reassuring sense of familiarity at a time of mass anxiety and threat. Through the conflict, sport became increasingly regarded as characteristic of Britishness; a symbol of the 'ordinary' everyday lives in defence of which the war was being fought. Utilised to support the welfare of war workers, the entertainment of service personnel at home and abroad and the character formation of schoolchildren and young citizens, sport permeated wartime culture, contributing to new ways in which the British imagined the past, present and future. Using a wide range of personal and public records - from diary writing and club minute books to government archives - this book breaks new ground in both the history of the British home front and the history of sport"--